Species-Specific Interactions of Bacillus Innocula and Arbuscular Mycorrhizal Fungi Symbiosis with Winter Wheat - Thomas I. Wilkes; Douglas J. Warner; Veronica Edmonds-Brown; Keith G. Davies (Microorganisms, 2020)
Arbuscular mycorrhizal (AM) fungi establish close interactions with host plants, an estimated 80% of vascular plant species. The host plant receives additional soil bound nutrients that would otherwise not be available. Other components of the microbiome, such as rhizobacteria, may influence interactions between AM fungi and the host plant. Within a commercial arable crop selected rhizobacteria in combination with AM fungi may benefit crop yields. The precise nature of interactions between rhizobacteria and AM fungi in a symbiotic relationship overall requires greater understanding. The present study aims to assess this relationship by quantifying: (1) AM fungal intracellular root structures (arbuscules) and soil glomalin as an indicator of AM fungal growth; and (2) root length and tiller number as a measure of crop growth, in response to inoculation with one of three species of Bacillus: B. amyloliquefaciences, B. pumilis, or B. subtilis. The influence of soil management, conventional (CT) or zero tillage (ZT) was a further variable evaluated. A significant (p < 0.0001) species-specific impact on the number of quantifiable AM fungal arbuscules was observed. The inoculation of winter wheat (Triticum aestivum) with B. amyloliquefaciences had a positive impact on AM fungal symbiosis, as indicated by an average of 3226 arbuscules per centimetre of root tissue. Bacillus subtilis increased root length significantly (p < 0.01) but decreased fungal symbiosis (p < 0.01). The inoculation of field soils altered the concentration of glomalin, an indicator of AM fungal growth, significantly (p < 0.00001) for each tillage treatment. The greatest increase was associated with B. amyloliquefaciences for both CT (p < 0.0001) and ZT (p < 0.00001). Bacillus subtilis reduced measured glomalin significantly in both tillage treatments (p < 0.0001 and p < 0.00001 for CT and ZT respectively). The interaction between rhizobacteria and AM fungi is variable, being beneficial or detrimental depending on species. This relationship was evident in both tillage treatments and has important implications for maximizing symbiosis in the crop plant-microbiome present in agricultural systems.